The Communication Strategies on Tourist Guide Professionalism in Lombok West Nusa Tenggara - Hanan, Ahmad; Sugianto, Sugianto (JOLLT Journal of Languages and Language Teaching, 2021)
This study was aimed at finding out the communication strategies on tourist guide professionalism in Lombok West Nusa Tenggara. The main research question raised in the study was â€œHow the communication strategies were used by the tour guides in terms of being professional tourists guides â€. The research was categorized into a descriptive qualitative study where the researcher used purposive sampling with a specific subset of people to find out the exact criteria of respondents. The researcher adopted snowball techniques in describing and interpreting the role of self-presentation on tourist guide professionalism. There were five tourist guides on the bus tour in their videos recorder and questionnaires towards communication strategies ofÂ  English speech manner regarding tourist guidesâ€™ professionalism. The sample was purposively taken by involving the guided cruise ship passenger tour at Lembar harbor. The result of the study found that the tourist guideâ€™s professionalism with the role of self-presentation was positively related with the categories of self-promotion, Ingratiation, supplication, exemplification, and Intimidation. Further, it was found as well that the tourist guides professionalism performances were positively related to the role of communication strategies under five main categories. The study concluded that five communication strategies were used by the tourist guide those are (1) Paraphrase with various Subcategories Approximation, WordÂ  Coinage, and Circumlocution (2). Transfer with two elements: (a) Literal Translation (b) Language Switch (3). Appeal for Assistance. (4). Mime (5). AvoidanceÂ  Strategy consists of two subcategories (a) TopicÂ  Avoidance andÂ  (b)Â  Message Abandonment.